2017
DOI: 10.1017/wet.2017.13
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Herbicide-Resistant Annual Bluegrass (Poa annua) Phenotypes with Methiozolin

Abstract: Methiozolin is an isoxazoline herbicide being investigated for selective POST annual bluegrass control in managed turfgrass. Research was conducted to evaluate methiozolin efficacy for controlling two annual bluegrass phenotypes with target-site resistance to photosystem II (PSII) or enolpyruvylshikimate-3-phosphate synthase (EPSPS)-inhibiting herbicides (i.e., glyphosate), as well as phenotypes with multiple resistance to microtubule and EPSPS or PSII and acetolactate synthase (ALS)-inhibiting herbicides. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Annual bluegrass phenotypes with resistance to ALS (R3, R7), EPSPS (R5), and PSII (R3, R4) inhibitors were included in our experiments. Resistance in all of these phenotypes was target-site based and has been described by Brosnan et al (2017). An herbicide susceptible phenotype from University Park, PA was included in all experiments as well.…”
Section: Methodsmentioning
confidence: 78%
“…Annual bluegrass phenotypes with resistance to ALS (R3, R7), EPSPS (R5), and PSII (R3, R4) inhibitors were included in our experiments. Resistance in all of these phenotypes was target-site based and has been described by Brosnan et al (2017). An herbicide susceptible phenotype from University Park, PA was included in all experiments as well.…”
Section: Methodsmentioning
confidence: 78%
“…Laboratory experiments revealed that this biotype exhibited reduced absorption and translocation of atrazine, as well as enhanced atrazine metabolism, compared to both herbicidesusceptible biotypes as well as those resistant to PSII-inhibiting herbicides via target-site mutation. Brosnan et al (2017a) observed that a biotype of annual bluegrass with target-site resistance to both ALS-and PSII-inhibiting herbicides (Brosnan et al 2016) was less sensitive to methiozolin (WSSA Group 30) at doses ranging from 0 to 8,000 g ha -1 and postulated that this response may be due to NTSR. Genetic investigations of this population revealed a differential expression of genes encoding an ABC Type-2 transporter (sixfold), as well as several cytochrome P450 enzymes and catalases (Brosnan et al 2019).…”
Section: Non-target Site Resistance (Ntsr)mentioning
confidence: 99%
“…Although there is debate over its exact MOA, it does appear that methiozolin has a novel MOA. Methiozolin effectively controls herbicide-susceptible annual bluegrass as well as biotypes with target site resistance to PSII, enolpyruvylshikimate-3-phosphate synthase (EPSPS), and mitotic inhibitor herbicides (Brosnan et al 2017;Koo et al 2014).…”
Section: Desire For New Mechanisms Of Action (Moas)mentioning
confidence: 99%
“…Despite these promising newly introduced or underdevelopment turfgrass herbicides, it is critically important that turfgrass managers understand that these new herbicides will not control all herbicide-resistant weeds, particularly those able to survive via non-target site resistance mechanisms. For example, Brosnan et al (2017) reported that, although methiozolin effectively controlled annual bluegrass with target site resistance to inhibitors of PSII, EPSPS, and cellular mitosis, it did not control a biotype reported to be resistant to ALS inhibitors via both target and non-target site resistance mechanisms. Turfgrass managers and weed scientists must also communicate that discovery of new herbicides with novel MOAs is a rare event and that a lack of new products is not exclusively a function of excessive regulation by those in national and/or state agencies.…”
Section: Desire For New Mechanisms Of Action (Moas)mentioning
confidence: 99%